Differences between peritoneal and pleural mesothelioma in Lombardy, Italy. (December 2017) - Mensi, Carolina; Mendola, Marco; Dallari, Barbara; Sokooti, Maryam; Tabibi, Ramin; Riboldi, Luciano; Consonni, Dario
Highlights: Occupational exposure was similar in peritoneal and pleural mesothelioma cases. Asbestosis and pleural plaques were more frequent in peritoneal mesothelioma cases. Employment in the asbestos-cement sector was more frequent in peritoneal cases. An association between asbestos exposure and peritoneal mesothelioma is confirmed. An association of high asbestos exposure with peritoneal mesothelioma is suggested. Abstract: Background: We examined characteristics of peritoneal (PEM) and pleural (PLM) mesothelioma in Lombardy, Italy. Methods: From the Lombardy Mesothelioma Registry we selected PEM (N = 300) and PLM (N = 5011) cases diagnosed in 2000–2014. We investigated asbestos exposure and presence of asbestosis or pleural plaques. Results: Incidence rates (per 1, 000, 000 person-years, world standardized) of PEM were 1.2 (men) and 0.9 (women), compared with 22.6 and 8.4 for PLM. Asbestosis (both genders) and pleural plaques (men) were more frequent among PEM cases. Occupational asbestos exposure was similar in PEM and PLM cases. We found higher proportions of PEMs employed in the asbestos cement production. Conclusion: The higher frequency of pleural plaques in PEM cases confirm the association between asbestos and peritoneal mesothelioma. The higher proportions of asbestosis and of past employment in the asbestos-cement sector among PEM cases suggest a possible role of high exposures to asbestos in the peritoneal mesothelioma genesis.